FT-IR Spectroscopic Studies for the Detection of Amino Acids in Sugarcane Status Infected with Red-rot - Raja Kumar, N.; Narayanaswamy, R. (Asian Journal of Chemistry, 2016)
An attempt has been made to investigate the status of amino acid content in resistant and red-rot disease infected sugarcane crop using FT-IR spectral study. From the present study it has been shown that FT-IR can be used for the detection of amino acids to a high degree of success and their status in both diseased and resistant varieties.